Clinical presentation of childhood leukaemia: a systematic review and meta-analysis. - Clarke, RT; Van den Bruel, A; Bankhead, CR; Mitchell, CD; Phillips, B; Thompson, MJ (BMJ Publishing Group, 2016)
Objective Leukaemia is the most common cancer of childhood, accounting for a third of cases. In order to assist clinicians in its early detection, we systematically reviewed all existing data on its clinical presentation and estimated the frequency of signs and symptoms presenting at or prior to diagnosis. Design We searched MEDLINE and EMBASE for all studies describing presenting features of leukaemia in children (0–18 years) without date or language restriction, and, when appropriate, meta-analysed data from the included studies. Results We screened 12 303 abstracts for eligibility and included 33 studies (n=3084) in the analysis. All were cohort studies without control groups. 95 presenting signs and symptoms were identified and ranked according to frequency. Five features were present in >50% of children: hepatomegaly (64%), splenomegaly (61%), pallor (54%), fever (53%) and bruising (52%). An additional eight features were present in a third to a half of children: recurrent infections (49%), fatigue (46%), limb pain (43%), hepatosplenomegaly (42%), bruising/petechiae (42%), lymphadenopathy (41%), bleeding tendency (38%) and rash (35%). 6% of children were asymptomatic on diagnosis. Conclusions Over 50% of children with leukaemia have palpable livers, palpable spleens, pallor, fever or bruising on diagnosis. Abdominal symptoms such as anorexia, weight loss, abdominal pain and abdominal distension are common. Musculoskeletal symptoms such as limp and joint pain also feature prominently. Children with unexplained illness require a thorough history and focused clinical examination, which should include abdominal palpation, palpation for lymphadenopathy and careful scrutiny of the skin. Occurrence of multiple symptoms and signs should alert clinicians to possible leukaemia.